A4.11 Syndecan-4 is an important player in regulating the WNT signalling pathway in articular cartilage. (13th February 2015) - Clarke, C; Held, A; Stange, R; Nalesso, G; Sherwood, J; Hansen, U; Godmann, L; Echtermeyer, F; Dell'Accio, F; Pap, T; Bertrand, J
Abstract : Background: The heparan sulfate proteoglycan syndecan-4 (Sdc4) is a regulator of various cartilage-related processes including osteoarthritis (OA). Blockade of Sdc4 signalling protects mice from cartilage degradation in experimentally induced OA. OA is characterised by matrix remodelling and hypertrophic differentiation of chondrocytes. Various signalling pathways including the WNT signalling pathway have been implicated to trigger this change of chondrocyte phenotype. Experiments investigating the effect of different WNT3a concentrations on chondrocytes have emphasised a complex dialogue between canonical and non-canonical WNT pathways. We hypothesise that Sdc4 controls the chondrocyte phenotype by specific modulation of WNT signalling pathways. Methods: In vitro analyses were performed using neonatal wild type (wt) and Sdc4-/- chondrocytes, or blocking antibodies against Sdc4. The influence of WNT3a on glycosaminoglycan (GAG) production was analysed using alcian blue staining of micromass cultures. Expression of marker genes (e.g. aggrecan, collagen2, MMP13) was measured by quantitative RT-PCR. Effects of WNT3a on canonical and non canonical WNT signalling were analysed using Western Blot (ß-catenin and pCamKII) and luciferase reporter assay (TCF/Lef). In vivo relevance was investigated upon induction of OA using the DMM model. Results: Micromass cultures revealed a higher basal GAG production by Sdc4-/- chondrocytes. WNT3a stimulation led to a decrease in GAG production in wt cells, which was absent in Sdc4-/- chondrocytes. qRT-PCR showed a 10x higher basal production of aggrecan and collagen2 in Sdc4-/- chondrocytes. WNT3a increased the expression of both genes in Sdc-4 -/-, whereas decreasing the expression in wt chondrocytes. MMP13 was significantly less expressed in Sdc4-/- chondrocytes and, unlike in wt cells, was not up regulated upon WNT3a stimulation. Western blot showed that ß-catenin is not up regulated upon stimulation with WNT3a in Sdc4-/- chondrocytes. LRP6 was less phosphorylated and TCF/Lef promotor was less activated upon WNT3a stimulation in Sdc4-/- chondrocytes. pCamKII was increased under basal conditions, but decreased upon WNT3a stimulation in Sdc4-/-. The same effects on canonical and non canonical WNT signalling upon WNT stimulation were obtained by using a blocking anti-Sdc-4 antibody. In vivo stainings confirmed in vitro results. Conclusion: Sdc4 is a major regulator of cellular response to WNT signals through facilitating the induction of the canonical WNT signalling pathway. The blockade of Sdc4 protects from OA induced changes in chondrocyte phenotype by inhibiting WNT induced differentiation of chondrocytes.